AN OUTPATIENT WITH ATRIAL FIBRILLATION: KEY FEATURES. THE FIRST DATA OF REKVAZA FP - YAROSLAVL REGISTER - V. V. Yakusevich; E. M. Pozdnyakova; Vl. .V. Yakusevich; V. A. Simonov; S. Yu. Martsevich; M. M. Loukianov; A. V. Zagrebelnyy; S. A. Boytsov (Рациональная фармакотерапия в кардиологии)
Aim. To study the clinical forms of atrial fibrillation (AF), cardiovascular risk factors and comorbidities in these patients; to perform monitoring of complications and mortality in AF; to assess the quality of diagnosis and treatment of AF in real outpatient practice.Material and methods. The register of patients with AF, visited an outpatient clinic of Yaroslavl from 01 January to 31 December 2013, was created. Quality of AF patient examination in the outpatient clinic was assessed. Morbidity and mortality of these patients were monitoring during 12 months by the contacts with patients, their relatives and doctors in charge.Results. The typical patient with AF has advanced age, mainly permanent AF and compromised history of cardiovascular diseases. 12-month monitoring of 212 outpatients with AF showed high mortality and the need for hospitalization due to cardiovascular diseases in this group. A total number of these patients was 99 or 46.7% of patients included into the register.Conclusion. The irregularity of observation and the lack of examination of patients with AF may be the reasons of the increased rates of mortality and complications in this group of outpatients.